Neuroinvasive West Nile virus infection in solid organ transplant recipients. Issue 1 (10th January 2023) - Kasule, Sabirah N.; Gupta, Simran; Patron, Roberto L.; Grill, Marie F.; Vikram, Holenarasipur R.
Abstract: Background: Literature on the natural course of neuroinvasive West Nile virus (WNV) infection in solid organ transplant (SOT) recipients is sparse. In the setting of a 2021 WNV outbreak in Arizona, we reviewed our institution's experience with neuroinvasive WNV infection in patients with SOT. Methods: We retrospectively identified SOT recipients treated for neuroinvasive WNV at Mayo Clinic in Arizona from 2007 through 2021. Clinical manifestations, disease course, and outcomes were analyzed. Results: Among 24 SOT recipients with WNV infection identified during the study period, 13 infections occurred in 2021. Most patients had gastrointestinal tract symptoms and fever at disease presentation. Five patients had cognitive impairment, and 14 initially or eventually had acute flaccid paralysis. Clinically significant deterioration occurred at a median of 4 (range, 1–11) days after hospital admission. Seventeen patients (71%) were transferred to the intensive care unit, with 15 requiring mechanical ventilation. Initial cerebrospinal fluid analysis mainly demonstrated a neutrophil‐predominant pleocytosis. Almost all patients ( n = 23) were treated with intravenous immunoglobulin alone or in combination with interferon alfa‐2b. Sixteen patients had clinical improvement, 4 of whom recovered completely. Six patients died during hospitalization due to complications of neuroinvasive WNV infection. Two patients were discharged to hospice without clinical recovery. The overall 30‐day mortality rate was 36%. Conclusion: Despite advances in supportive care, neuroinvasive WNV infection is associated with substantial morbidity and mortality in SOT recipients. Flaccid paralysis is an indicator of poor prognosis. Abstract :